2011
DOI: 10.1371/journal.pone.0028872
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Alpha-Myosin (MYH6) Is the Predominant Sarcomeric Disease Gene for Familial Atrial Septal Defects

Abstract: Secundum-type atrial septal defects (ASDII) account for approximately 10% of all congenital heart defects (CHD) and are associated with a familial risk. Mutations in transcription factors represent a genetic source for ASDII. Yet, little is known about the role of mutations in sarcomeric genes in ASDII etiology. To assess the role of sarcomeric genes in patients with inherited ASDII, we analyzed 13 sarcomeric genes (MYH7, MYBPC3, TNNT2, TCAP, TNNI3, MYH6, TPM1, MYL2, CSRP3, ACTC1, MYL3, TNNC1, and TTN kinase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 34 publications
(56 reference statements)
1
64
0
1
Order By: Relevance
“…8 Additional MLPA probes were used and family MC061 was found to have a 2q37.3 duplication. 8 Twenty-one families of this series were tested for a panel of 13 sarcomeric genes in a second collaborative study, 7 and disease-causing variants were found only in the alpha cardiac heavy chain myosin gene (MYH6), in three families (MC027 p.(Cys539Arg), MC053 p.(Lys543Arg) and MC081 p.(Arg17His)). These 21 families were selected out of the Registry because at least one affected individual had ASD (for details, see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Additional MLPA probes were used and family MC061 was found to have a 2q37.3 duplication. 8 Twenty-one families of this series were tested for a panel of 13 sarcomeric genes in a second collaborative study, 7 and disease-causing variants were found only in the alpha cardiac heavy chain myosin gene (MYH6), in three families (MC027 p.(Cys539Arg), MC053 p.(Lys543Arg) and MC081 p.(Arg17His)). These 21 families were selected out of the Registry because at least one affected individual had ASD (for details, see Supplementary Table S1).…”
Section: Discussionmentioning
confidence: 99%
“…Some families of this cohort were screened for other genes or another MLPA test and are reported elsewhere. 7,8 For details on the enrolled families, see Supplementary Table S1. All variants were submitted to LOVD (www.lovd.nl/3.0/home).…”
Section: Genetic Analysismentioning
confidence: 99%
“…[38][39][40][41] To our knowledge, there has been no previous report of cardiomyopathy in patients with CHD who harbor a heterozygous MYH6 mutation. Moreover, there has been no clear correlation between the MYH6 domain in which the mutation resides and cardiac phenotype.…”
Section: Dominant Myh6 Mutations In Chd or Cardiomyopathymentioning
confidence: 91%
“…Heterozygous MYH6 mutations associated with cardiomyopathy trend toward later disease onset, 35,36 consistent with the latent systolic dysfunction observed in carriers of compound heterozygous MYH6 mutations. Dominant MYH6 mutations associated with CHDs have variable penetrance as highlighted by segregation studies of familial atrial septal defect, [38][39][40] which revealed several mutation carriers without structural heart disease. Variable intrafamilial expression was also demonstrated in a family where 4 MYH6 mutation carriers had a range of phenotypes including bicuspid aortic valve, coarctation of the aorta, ventricular septal defect, and subaortic stenosis.…”
Section: Dominant Myh6 Mutations In Chd or Cardiomyopathymentioning
confidence: 99%
“…Various mutations in transcription factors and sarcomeric genes were described in different studies [3]. We have analyzed different genes involved in the pathogenesis of CHDs and could identify mutations in ASD patients [4,5,6].…”
Section: Introductionmentioning
confidence: 99%